نموذج التعلم القائم على المشروع من خلال أنشطة المناظرة لتعزيز مهارة الكلام - Masturi, Masturi; Syafitri, Nila Sari; Fadllurrahman, Moh.; Widadi, Widadi; Huda, Hisbullah (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2026)
Arabic language instruction in pesantren remains largely lecture-based and provides limited opportunities for speaking practice, creating a gap between grammatical mastery and oral communicative competence. This study examines the effectiveness of Project-Based Learning (PjBL) implemented through debate activities in improving speaking skills at Darul Lughah al-‘Arabiyyah wa al-Fiqh as-Salafi, Annuqayah Latee Islamic Boarding School. A quasi-experimental design with two non-randomized groups was employed: an experimental group applying PjBL–Debate and a control group engaging in conventional debate, each consisting of 15 students. Data were collected through performance-based speaking tests and observations and analyzed using descriptive statistics, paired and independent t-tests, and N-Gain scores. The findings indicate that PjBL–Debate is significantly more effective than conventional debate in enhancing students’ speaking skills. The experimental group’s mean score increased from 56.8 to 84.6 (p < 0.001) with a high N-Gain of 0.71, while the control group showed only modest improvement (N-Gain = 0.31). These results suggest that integrating PjBL with debate effectively promotes contextual, communicative, and collaborative Arabic use within the pesantren language environment, offering a practical strategy to bridge theoretical knowledge and oral proficiency.